An analysis of the tripartite evolutionary game for building the ecological security barrier in the Bohai Sea under the threshold of land-sea integration - Luan, Di; Cao, Hongjun; Qu, Tongkun (Frontiers in Marine Science, 2024)
The construction of marine ecological security barriers (MESBs) is fundamental for the sustainable development of the marine ecological environment and of the marine economy, and is an important component of the strategy of land-sea integration. It is difficult to build an effective MESB simply by relying on the power of the government; therefore, to this respect, it is urgent to encourage the multiple participating subjects to work together. This study takes the Bohai Sea as the research object, and uses evolutionary game theory to construct a game model of decision-making behavior among marine enterprises, local governments, and the public in the process of construction of the MESB in the Bohai Sea, so as to explore the strategic stability equilibrium point through the analysis of the interests of the three decision makers, and lay the foundation for promoting this process. The results are as follows: (1) Local government regulation is key to promote the transformation of the Bohai Sea MESB from policy documents to behavior and from goal to practice; moreover, it directly influences whether the main sources of land-based pollution, i.e., marine enterprises, will abandon the traditional approach to production and development and actively promote the construction of the Bohai Sea MESB. (2) The supervision and reporting of the public can be used as a synergistic, auxiliary supervision means. Thanks to the government’s publicity and education, the public will develop social awareness of marine ecological security, which in turn will ensure a better public supervision of the behavior of local governments and, thus, promote the active participation of marine enterprises in the MESB in the Bohai Sea. (3) Participation costs, ecological benefits, corporate social image, fines, and other factors are the main factors considered in the strategic choice of marine enterprises, with different factors having different marginal effects at different stages. Finally, this study proposes effective measures to further clarify the roles and functions of the stakeholders in the construction of the MESB in the Bohai Sea, balance the interests of the game subjects, and provide an effective implementation path for the realization of the “Ocean Power”.